Establishment of in vitro breast cancer bone metastasis model using an artificial microenvironment - Smith, Sarah (My University, 2021)
Advanced breast cancer frequently metastasises to the bone, causing considerable morbidity to the patients. Survival rate after detection of bone metastases is poor, and options to treat bone metastases are insufficient. The bone microenvironment provides a fertile ground for the breast cancer cells to migrate and populate to. Tumour cells and the microenvironment have complicated and dynamic interactions that induce altered activity and phenotype in tumour cells. Novel preclinical models are needed in cancer drug development for efficient selection process of drug candidates. The aims of this thesis study were to establish an in vitro artificial bone microenvironment and to investigate possible altered sensitivity of metastatic breast cancer cells to cytotoxic agents in the formed microenvironment. The artificial bone microenvironment was established by culturing MC3T3-E1 cells with the bioactive glass. Osteoblast differentiation was verified with alkaline phosphatase staining and mineralisation capability with von Kossa staining. Altered sensitivity of breast cancer cells to cytotoxic drugs was studied by incorporating 4T1-Luc2 and using a luciferase reporter assay to evaluate cell viability after treatment. The results of this thesis study showed that osteoblasts cultured together with S5P34 bioactive glass formed a functional microenvironment and osteoblast were able to differentiate and secrete mineralised matrix in it. An interesting finding was that 4T1-Luc2 cells had increased sensitivity to 5-fluorouracil when cultured in artificial microenvironment when compared to cultures solely on plastic. The same effect wasn’t observed with doxorubicin. The artificial bone microenvironment model proved attractive possibility and development of complex metastasis models should be continued.